2019
DOI: 10.1021/acsami.9b13948
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance WSe2 Photodetector Based on a Laser-Induced p–n Junction

Abstract: Two-dimensional heterojunctions exhibit many unique features in nanoelectronic and optoelectronic devices. However, heterojunction engineering requires a complicated alignment process and some defects are inevitably introduced during material preparation. In this work, a laser scanning technique is used to construct a lateral WSe2 p–n junction. The laser-scanned region shows p-type behavior, and the adjacent region is electrically n-doped with a proper gate voltage. The laser-oxidized product WO x is found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…In our study, most pristine WSe 2 transistors (from few layers to about 20 nm) showed an electrondominated transport behavior (Figure 1b), which were then p-type doped by laser irradiation. Different from previous reports where high laser power density was used and obvious sample thinning was observed, [38,40] less focused laser was used here to avoid severe ablation of samples (Figure S1, Supporting Information) and hole doping could be achieved without obvious sample thinning (Figure S3, Supporting Information). Figure 1c shows the transfer curves of a typical WSe 2 transistor before and after a series of laser irradiation (by a laser scanning at the speed of 0.495 µm s −1 with the power density changing from 3.48 to 7.40 mW µm −2 ).…”
Section: Laser Irradiation Induced P-type Doping Of Wsementioning
confidence: 98%
See 2 more Smart Citations
“…In our study, most pristine WSe 2 transistors (from few layers to about 20 nm) showed an electrondominated transport behavior (Figure 1b), which were then p-type doped by laser irradiation. Different from previous reports where high laser power density was used and obvious sample thinning was observed, [38,40] less focused laser was used here to avoid severe ablation of samples (Figure S1, Supporting Information) and hole doping could be achieved without obvious sample thinning (Figure S3, Supporting Information). Figure 1c shows the transfer curves of a typical WSe 2 transistor before and after a series of laser irradiation (by a laser scanning at the speed of 0.495 µm s −1 with the power density changing from 3.48 to 7.40 mW µm −2 ).…”
Section: Laser Irradiation Induced P-type Doping Of Wsementioning
confidence: 98%
“…Previously, Seo et al reported p-type doping of MoTe 2 by laser scanning on the electrodes, which provides an alternative way to control the carrier type. [37] Chen and Yang et al [38,39] reported the in-plane WSe 2 PN junctions using laser ablation. However, the doping mechanism and the PN junction profile were not sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) Laser-induced oxidation of WSe 2 . Reproduced with permission [222]. Copyright 2019, American Chemical Society.…”
mentioning
confidence: 99%
“…These advances include enhanced contact performance [32,88] and greater control of active channel parameters. [113] Applications in electronics include 2D-material-based transistors [13,16,19,104,[114][115][116][117][118] and memory devices. [119][120][121][122]…”
Section: Electronic Applicationsmentioning
confidence: 99%